Substrate level versus oxidative phosphorylation in the generation of ATP in Thiobacillus denitrificans - Aminuddin, M. (Springer-Verlag, 1980)
Particulate fractions of Thiobacillus denitrificans catalyse the phosphorylation of ADP to ATP during the oxidation of various inorganic sulphur compounds or NADH via an electron transport chain. On the other hand, a "soluble" cell-free fraction synthesized ATP from APS and inorganic phosphate. The production of ATP was verified either by the firefly luciferin-luciferase enzyme system or by the incorporation of 32Pi into ATP. During the oxidation of sulphide, sulphite and NADH the production of ATP from ADP by particulate fractions is inhibited by compounds that inhibit electron transfer and by uncouplers of oxidative phosphorylation. However, these compounds had little effect on the production of ATP from AMP during the oxidation of sulphite by the soluble fraction. NADH was the most effective electron donor for oxidative phosphorylation. The soluble fraction contained high activities of ATP sulphurylase, inorganic pyrophosphatase and adenylate kinase but ADP sulphurylase activity was relatively low. The effects of inhibitors on ATP production from APS and Pi are compared with those on adenylate kinase and ATP sulphurylase. © 1980 Springer-Verlag.